Factors Influencing Safe Wayfinding Behaviour at Sports Complex Surface Access in Universiti Utara Malaysia - Anuar, Nur Khairiel; Sabar, Rohafiz; Ahmad, Za'im (2020)
Wayfinding is a process in which people navigate a landside environment using information support systems. A movement of process or activity which involves adaptive displays as directional signs and accurately following the planning and route is maintained. This paper explains the factors influence safe wayfinding behaviour from surface access of campus main entrance to sports complex in Universiti Utara Malaysia (UUM). The importance of wayfinding strategy and their influence on the decision- making process for the provision of sports complex road access wayfinding was considered. The Mean, Standard Deviation (SD) and Two-Way ANOVA test were used to analyse the results and discussed with reference to the general needs as standard design of sports complex access and take into account the preference general users’ experience. The contributory factors were then analysed and presented; risk to collisions, speed exceedances, centreline crossing and road edge excursions. The results show that there is a relationship between wayfinding and surface access design. Although many studies have been conducted on wayfinding in general, a detailed evaluation on safe wayfinding behaviour at sports complex were still unexplored domains